Simulation fails to replicate stress in trainees performing a technical procedure in the clinical environment. (2nd January 2017) - Baker, B. G.; Bhalla, A.; Doleman, B.; Yarnold, E.; Simons, S.; Lund, J. N.; Williams, J. P.
Abstract: Introduction: Simulation-based training (SBT) has become an increasingly important method by which doctors learn. Stress has an impact upon learning, performance, technical, and non-technical skills. However, there are currently no studies that compare stress in the clinical and simulated environment. We aimed to compare objective (heart rate variability, HRV) and subjective (state trait anxiety inventory, STAI) measures of stress theatre with a simulated environment. Methods: HRV recordings were obtained from eight anesthetic trainees performing an uncomplicated rapid sequence induction at pre-determined procedural steps using a wireless Polar RS800CX monitor © in an emergency theatre setting. This was repeated in the simulated environment. Participants completed an STAI before and after the procedure. Results: Eight trainees completed the study. The theatre environment caused an increase in objective stress vs baseline ( p = .004). There was no significant difference between average objective stress levels across all time points ( p = .20) between environments. However, there was a significant interaction between the variables of objective stress and environment ( p = .045). There was no significant difference in subjective stress ( p = .27) between environments. Discussion: Simulation was unable to accurately replicate the stress of the technical procedure. This is the first study that compares the stress during SBT with the theatre environment and has implications for the assessment of simulated environments for use in examinations, rating of technical and non-technical skills, and stress management training.